Analisis Perhitungan Hargar Pokok Produksi Air Sebagai Dasar Penentuan Harga Jual Air Pada Perumda Tirta Pakuan Kota Bogo - Nafisatul Amini; Andy Lasmana; Maria Magdalena Melani (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2024)
This research was conducted to find out the calculation of the cost of production of water as a basis for determining the selling price of water at the Tirta Pakuan Regional Drinking Water Company (Perumda), Bogor City. This research is intended to find out the calculation of the cost of production of water using the full costing method. Perumda Tirta Pakuan, Bogor City, has used the tariff set by the Bogor Regency government, namely based on the basic price of water production. This study uses descriptive analysis research with a quantitative approach. The results of the research that has been carried out show that the cost of water production at Perumda Tirta Pakuan Bogor City in 2019 is Rp. 4,025.73/m3, in 2020 Rp. 4,098.24/m3 , and in 2021 it is Rp. 3,952.81/m3 higher than the cost of producing water according to the full costing theory or method, namely in 2019 Rp. 2,509.78, in 2020 Rp. 2,407.10, and in 2021 it is Rp. 2,340.34. Meanwhile, the selling price of Perumda Tirta Pakuan water, Bogor City, by calculating the average tariff, namely in 2019, is Rp. 6,856.32, in 2020 Rp. 6,471.84, and in 2021 it is Rp. 6651.32. It can be seen that the cost of production is below the selling price of water. So that the selling price can fully cover operating expenses, which means the company will experience profits in 2019-2021.